Association between CYP2C19*2 variant and clinical outcome in Clopidogrel treated patients from Republic of Macedonia - Aleksandra Kapedanovska Nestorovska; Aleksandra Dimitrovska Cvetkovska; Ljubica Suturkova (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2011)
Clopidogrel is the thienopyridine of choice for prevention of ischemic events and stent thrombosis in patients with atherotrombotic disease. Recent studies suggest that certain genetic variants involving CYP450 system are responsible for wide interindividual variability in treatment response profiles among clopidogrel treated individuals. The aim of this study was to define the prevalence of most common CYP2C19*2: 681G>A (rs4244285) allelic variant in Macedonian population and determine the risk association with major cardiovascular adverse events in clopidogrel treated patients with atherotrombotic cardiovascular disease. CYP2C19 *2 genotype was assessed in 198 subjects from R.Macedonia. The association between the reduced function CYP2C19 *2 A allele and clinical outcome was evaluated in 67 clopidogrel treated patients within a follow up period of at least 6 months (from 6 to 60 months) after initializing clopidogrel therapy. The population frequency of polymorphic A allele responsible for impaired clopidogrel metabolism in Macedonian population was 0.18. CYP2C19*2 variant was significantly associated with increased rate of adverse cardiovascular events in the allelic (OR= 3.188; 95% CI= 1.437-7.058), dominant (OR=3.477; 95% CI= 1.256-9.630) and co-dominant model ( OR=6.750, 95% CI: 1.186-38.410) of statistical analysis (adjusted OR= 2.619; Ptrend=0.0088). The influence of CYP2C19*2 was most strongly correlated with worse event free survival in patients carrying AA genotype (log rank P = 0.0024) and patients carrying at least one CYP2C19*2 reduced function allele (log rank P=0.0058). CYP2C19*2 genetic variant in the population from Republic of Macedonia has similar distribution as determined in other European populations. Carriage of reduced function CYP2C19 *2 allele is associated with worse event free survival in clopidogrel treated patients with atherotrombotic disorders.